Nonlinear Viscoelastic Properties of 3D-Printed Tissue Mimicking Materials and Metrics to Determine the Best Printed Material Match to Tissue Mechanical Behavior - Verga, Adam S.; Tucker, Sarah Jo; Gao, Yuming; Plaskett, Alena M.; Hollister, Scott J. (Frontiers in Mechanical Engineering, 2022)
3D Printed biomaterials have become ubiquitous for clinical applications including tissue mimicking surgical/procedure planning models and implantable tissue engineering scaffolds. In each case, a fundamental hypothesis is that the printed material mechanical properties should match those of the tissue being replaced or modeled as closely as possible. Evaluating these hypotheses requires 1) consistent nonlinear elastic/viscoelastic constitutive model fits of 3D printed biomaterials and tissues and 2) metrics to determine how well 3D printed biomaterial mechanical properties match to a corresponding tissue. Here we utilize inverse finite element modeling to fit nonlinear viscoelastic models with a Neo-Hookean kernel to 29 Polyjet 3D printed tissue mimicking materials. We demonstrate that the models fit well with R2 > 0.95. We also introduce three metrics (least squares difference, Kolmogorov-Smirnov statistics, and area under stress/strain or load/displacement curve) to compare printed material properties to tissue properties. All metrics showed lower values for better matches between 3D printed materials and tissues. These results provide a template for comparing 3D printed material mechanical properties to tissue mechanical properties, and therefore a basis for testing the fundamental hypotheses of 3D printed tissue mimicking materials.